Characteristics of neurodynamic properties in volleyball players of different skill levels - Bondar, R. (Journal of Education, Health and Sport, 2025)
Statistical data on the psychophysiological indicators of high-qualification volleyball players are presented and compared with lower-qualification volleyball players. Characteristics of sensorimotor skills, feedback, rhythm, reaction to a moving object, and the tapping test are shown. A link was established between the autonomic nervous system and the improvement of individual-typological characteristics of the higher nervous activity of volleyball players. The aim of the research was to determine and compare the psychophysiological state indicators of healthy volleyball players and those with hearing impairments, as well as to compare the results of high-qualification volleyball players with lower-qualification ones. To accomplish this task, 18 high-qualification volleyball players with Master of Sports (MS) or Candidate for Master of Sports (CMS) titles, who have hearing impairments—full or partial sensory deprivation ("GROUP 1", KKLPU volleyball team) - and 8 qualified volleyball players (CMS and lower ranks, "GROUP 2", NUPESU volleyball team) were selected. The age of the subjects varied significantly, ranging from 18 to 36 years. Based on the analysis of literature on the chosen research topic, a lack of scientific study regarding this issue specifically in volleyball was identified. The obtained indicators allow for the assessment of the individual level of the psychophysiological state of high-qualification volleyball players in comparison with lower-qualification players.